2018
DOI: 10.1387/ijdb.170341fw
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis, regeneration and tumour formation in the mammalian epidermis

Abstract: The epidermis is the outer covering of the skin and provides a protective interface between the body and the environment. It is well established that the epidermis is maintained by stem cells that self-renew and generate differentiated cells. In this review, we discuss how recent technological advances, including single cell transcriptomics and in vivo imaging, have provided new insights into the nature and plasticity of the stem cell compartment and the differing roles of stem cells in homeostasis, wound repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 107 publications
0
35
0
1
Order By: Relevance
“…The skin epithelium renews throughout life in a continuous turnover ensured by stem and progenitor cells that balance proliferation and differentiation to replace dead and terminally differentiated cells 1,13,14 . Epithelial stem cells reside in a specific microenvironment called niche that is composed of a variety of cell types.…”
Section: Skin Epithelial Stem Cells During Homeostasis [H1]mentioning
confidence: 99%
See 1 more Smart Citation
“…The skin epithelium renews throughout life in a continuous turnover ensured by stem and progenitor cells that balance proliferation and differentiation to replace dead and terminally differentiated cells 1,13,14 . Epithelial stem cells reside in a specific microenvironment called niche that is composed of a variety of cell types.…”
Section: Skin Epithelial Stem Cells During Homeostasis [H1]mentioning
confidence: 99%
“…Niche cells influence stem cell behaviour directly by cell contact or indirectly via ECM components and growth factors 15 . Although skin stem cells are able to regenerate the entire repertoire of skin epithelial lineages upon transplantation, lineage tracing has demonstrated that during physiological conditions, epidermal compartments are sustained by their own pool of resident stem cells [14][15][16] (Fig. 2a).…”
Section: Skin Epithelial Stem Cells During Homeostasis [H1]mentioning
confidence: 99%
“…While the two principles are not mutually exclusive, an intrinsic niche is perhaps particularly suitable in the context of large SC populations that need to homogeneously generate progeny cells over extended distances, such as NSC niches or the interfollicular SC population in the adult mammalian skin (Belokhvostova et al, 2018;Blanpain and Fuchs, 2009). Interestingly, in the latter case, a recent study using intravital imaging showed that neighboring SCs coordinate their fate decisions to differentiate and divide (Mesa et al, 2018).…”
Section: Lineage-derived Inhibitory Feedbacks Generate An Intrinsic Nmentioning
confidence: 99%
“…Таким образом, репаративный потенциал кожи определяет характер ее морфофункциональных преобразований, косметический результат раневых процессов [57,79]. Концептуальный подход к пониманию молекулярных механизмов нейроиммуноэндокринной регуляции физиологических и патофизиологических процессов в коже [81,85,91,92,93,95] позволит расширить возможности управляемой регенерации в случае повреждения кожи, объективного контроля за течением репаративных процессов в ней.…”
Section: заключениеunclassified